Human Health Risks due to Exposure to Water Pollution: A Review - Babuji, Preethi; Thirumalaisamy, Subramani; Duraisamy, Karunanidhi; Periyasamy, Gopinathan (Water (Basel), 2023)
Water resources are crucial in developing any area as they serve as a major source of potable, agricultural, and industrial water. Water contamination, caused by natural and anthropogenic activities, poses a significant threat to public health globally. This review synthesizes data from various studies published in national and international journals, as well as reports from governmental and non-governmental organizations. Our primary objective is to understand and review previous research on water pollution, contamination types, and the effects of water contamination on public health. Water pollution studies generally involve a scientific understanding of the biological, chemical, and physical processes that control the movement of contaminants in the underground environment. The nature and severity of health consequences vary based on several factors, including the chemical composition, duration of exposure, and concentration of pollutants. This work highlights the human health risks associated with current research topics such as anthropogenic, geogenic, microplastics, pharmaceuticals, and heavy metals. A section on remedial measures and mitigation strategies is included to emphasize sustainable approaches to water conservation, replenishment, and sustainability. However, there is a lack of comprehensive knowledge regarding the distribution, toxic effects, and human health risks associated with different sources of contamination. This review thus establishes links between multiple sources of pollution, their toxicity to human health, and approaches to health risk assessment.